2009
DOI: 10.1093/ndt/gfp073
|View full text |Cite
|
Sign up to set email alerts
|

The value of post-biopsy ultrasound in predicting complications after percutaneous renal biopsy of native kidneys

Abstract: We find that with the use of renal ultrasound 1-h post-PRB, the absence of perinephric bleeding is predictive of an uncomplicated course while the presence of a perinephric haematoma is not reliably predictive of a clinically significant complication post-renal biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
97
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 27 publications
3
97
1
Order By: Relevance
“…Identifying a perinephric hematoma after renal biopsy is a therapeutic dilemma because hematoma alone is not predictive of a complicated post-biopsy course (14). Traditional teaching would recommend two options; first, the patient can be observed closely as the hemorrhage frequently settles spontaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying a perinephric hematoma after renal biopsy is a therapeutic dilemma because hematoma alone is not predictive of a complicated post-biopsy course (14). Traditional teaching would recommend two options; first, the patient can be observed closely as the hemorrhage frequently settles spontaneously.…”
Section: Discussionmentioning
confidence: 99%
“…With this limitation, it was not possible to identify cases where there were minor hemorrhagic complications. Previous work has indicated that a high proportion of patients will acquire a small hematoma after a renal biopsy, whatever the underlying diagnosis (20,25). However, these are unlikely to be of clinical significance, and it can be argued that their detection is unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…However, the absence of hematoma at 1 h was highly predictive of an uncomplicated course [35] . Waldo et al [36] showed that patients which did not present perinephric hematoma one hour after biopsy did not develop major complications in 95% of cases, while the presence of hematoma was predictive for major complications in 43%. Therefore, the routine use of ultrasound at 1 h after PRB may have a role in determining an uncomplicated course [36] .…”
Section: Perinephric Hematomamentioning
confidence: 99%